Making meaning of vocabulary learning: seizing opportunities at oppportune moments - Naginder Kaur, (Penerbit UKM, 2015)
The ability in making meaning of learning through opportunities is seen as a pathway to autonomous learning behaviour. This study is undertaken to explore the behaviours of a group of nine learners at a tertiary institution in Malaysia to see how they utilise both receptive as well as productive vocabulary learning opportunities meaningfully beyond their English language course. The theory of constructivism appertains, as the learning activity is active, constructive, cumulative and goal-directed. The participants‟ journal entries of one month were perused to enquire the various aspects of their learning experiences and what they did before, during and after English language class. Weekly retrospective in depth interviews were conducted with the participants, as well as their class lecturer. The study found that these learners lacked proactive attitude in seizing learning opportunities and were poor readers of English language materials. The study also found that the extent learners take learning opportunities is not solely dependent on their language proficiency, but more than that on learner confidence and their preferred learning style of non-verbal learning, hence dispelling the widely accepted belief that high proficiency learners are more proactive in their learning pursuits. In seizing learning opportunities at opportune moments, the major stumbling blocks are lack of transfer in learning as well as limited and untapped communication opportunities with the lecturer beyond class hours. This study shows that average and low ability learners can also embrace learning opportunities meaningfully with other moderating variables, such as a confident personality and adequate risk taking initiatives.